Qualitative and Quantitative Detection of Virulence-Associated Genes in Escherichia Coli Isolates from Women with Urinary Tract Infections - Zainab Hussein Mahdi; Lina S. Alsaadi; Zainab Amer Hatem; Saade Abdalkareem Jasim (Acta Biologica Slovenica)
Escherichia coli is the most common type of Enterobacteriaceae family that causes urinary tract infections. This bacterium causes diseases due to its many virulence factors. During the study, (150) urine samples were collected for women with symptoms of UTIs aged between (20-50) years from 1/9/2021 to 1/4/2022. Forty-five isolates of E. coli were diagnosed using a biochemical test, a VITEK2 system, and molecular detection using traditional PCR. A molecular study was conducted on 25 of these isolates using conventional PCR and qRT-PCR to investigate the presence of genes included (16S rRNA, uidA,  fimA and kpsMTII). The traditional PCR results showed the presence of both 16S rRNA and uidA gene in all 25 isolates of E. coli. In contrast, the results showed that  23 (92%) and 18 (72%) isolates possessed fimA and kpsMTII genes, respectively. Following the extraction of RNA from twenty-five pathogenic isolates of E. coli and ten non-pathogenic isolates, gene expression of fimA and kpsMTII was quantified using quantitative real-time reverse transcription PCR (qRT-PCR). The observed fold change indicates a potential overexpression of the KSPMII and FimA genes in uropathogenic E. coli. The expression of the kpsMTII gene showed the highest level of folding with an average of 22.89 in the case of uropathogenic E.coli isolates compared with non-pathogenic isolates (control) with an average of 4.11. While the expression of the fimA gene with the highest level of fold change with an average of 90.52 in the case of uropathogenic E.coli isolates compared with non-pathogenic isolates (control) with an average of 0.94, Significant differences were observed among the isolates, as indicated by P values less than 0.05. This finding demonstrated that qRT-PCR detects genes that were expressed in comparison with traditional PCR. Also, qRT-PCR is a more sensitive and accurate assay than conventional PCR for determining the quantitative prevalence of E. coli in urine samples.